Facile fabrication of SiO2 nanotubes coated with nitrogen-doped carbon layers as high-performance anodes for lithium-ion batteries. Issue 1 (1st January 2021) - Zhang, Xi; Li, Ke; Li, Yanbo; Liu, Jinjie; Dai, Jintao; Li, Yifan; Ai, Fanrong
Abstract: Silica-based anodes have attracted considerable attention because of their low discharge potential and high theoretical specific capacity. Herein, SiO2 nanotubes (SNTs) were prepared via the sol-gel method with an ammonium dl -tartrate template, followed by the coating of N -doped carbon layers on their surface through a simple dopamine self-polymerization. The unique hollow tubular structure can accommodate large volume expansions. Notably, N -doped carbon layers play a crucial role in enhancing the SiO2 conductivity and increasing the Li + diffusion rate. Furthermore, SNTs with high specific surface areas provide numerous sites for electron and Li + insertion during lithiation. Hence, under the combined effect of the above-mentioned properties, N -doped carbon-coated SNTs (SNTs@NC) composites exhibited excellent cycling and rate performances. At a current density of 100 mA g −1, SNTs@NC composites delivered a reversible specific capacity of 781 mA h g −1 after the 200th cycle. Even at 1 A g −1, the composites achieved a value of 522 mA h g −1 . With such excellent electrochemical properties, SNTs@NC composite material can serve as the next-generation anode for lithium-ion batteries.